Persepsi Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha Pada Penggunaan E-wallet Sebagai Alat Pembayaran E-commerce - Josephine Tita Arquette; I Putu Arya Dharmayasa (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2023)
This study aims to analyze in depth the perceptions of students of the Faculty of Economics, University of Education of Ganesha on the use of e-wallets as a means of payment for e-commerce. This type of research is descriptive quantitative with data collection methods in the form of questionnaires, but first tested for validity and reliability. The number of samples used is 348 respondents. The sampling technique used was a proportionate stratified random sampling technique and the sample decision was based on certain criteria, namely students of the Faculty of Economics, University of Education, Ganesha who used e-wallets and students who had made e-commerce payments using e-wallets. The data analysis technique used is descriptive analysis. The results of this study indicate: (1) The perception of students of the Faculty of Economics, University of Education in Ganesha on the use of e-wallets as a means of payment for e-commerce in terms of the dimensions of perceived usefulness has a score of 4,821 with the criteria of strongly agreeing (2) Perceptions of students of the Faculty of Economics, University of Education Ganesha on the use of wallets as a means of payment for e-commerce in terms of perceived ease of use dimensions has a score of 8,134 with criteria strongly agree (3) Perceptions of students of the Faculty of Economics, University of Education Ganesha on the use of wallets as a means of payment for e-commerce in terms of attitude toward dimensions using technology has a score of 2,307 with the criteria of strongly agreeing (4) Perceptions of students of the Faculty of Economics, University of Education of Ganesha on the use of wallets as a means of e-commerce payment in terms of the dimensions of behavioral intention to use has a score of 2,245 with criteria of strongly agreeing (5) Perceptions of students of the Faculty of Economics Ganesha University of Education on the use of wallets as a means of e-commerce payment in terms of the actual system usage dimension has a score of 2,231 with the criteria of agreeing.